AB0239 Association of A TRAF1 Gene Polymorphism with Joint Destruction in Anti-Citrullinated Peptide Antibody-Negative Patients with Rheumatoid Arthritis. (15th July 2016) - Yoshida, S.; Ikari, K.; Yano, K.; Matsumoto, M.; Nakamura, M.; Taniguchi, A.; Yamanaka, H.; Momohara, S.
Abstract : Background: Many studies show that heritability plays a part in joint destruction in rheumatoid arthritis (RA); however, the details are poorly understood. In the recent report by van Steenbergen et al., 43 polymorphism in a 66 Kb region spanning tumor necrosis factor receptor-associated factor 1 ( TRAF1 ) were associated with radiographic progression in anti-citrullinated peptide antibody (ACPA)-negative patients with RA in a multicohort study from Europe and North America. Specially, the polymorphisms were located in the area downstream of the complement component 5 ( C5 )- TRAF1 region and upstream to the TRAF1 -PHD finger protein 19 ( PHF19 ) region. We were intrigued by these findings and curious to know the relevance in Asian populations. Thus, we investigated the association of the 66 Kb region within C5 - TRAF1 - PHF19 with progression of joint destruction in Japanese patients with RA. Objectives: The purpose of this study was to identify genetic variants associated with progression of joint destruction in Japanese ACPA-negative patients with RA. Methods: We studied 120 ACPA-negative patients with RA for whom Sharp/van der Heijde scores (SHS) of the hands were available at 5-year disease duration. DNA samples of the subjects were obtained from the Institute of Rheumatology Rheumatoid Arthritis cohort study (IORRA) DNA collection. All of the patients consented to participate in this study in accordance with the process approved by the Tokyo Women's Medical University Genome Ethics Committee. Identification of tag single nucleotide polymorphisms (SNPs) in the C5 - TRAF1 - PHF19 region was performed using Haploview (version 4.2; minor allele frequency >0.05, pairwise r 2 >0.8). A total of 12 tag SNPs were selected and genotyped. We used rs2900180 as a proxy for rs7021880 (r 2 =1.0), which was the polymorphism with the lowest P -value found by van Steenbergen et al. Linear regression analyses were performed to examine the association between each SNP and log-transformed SHS. Results: The A allele of rs3761847 in TRAF1 was significantly associated with SHS in the recessive model ( P =0.00099, Table 1 ). The other SNPs had no association with SHS. Conclusions: Our study demonstrated that the A allele of rs3761847 in the TRAF1 gene was associated with joint destruction. We previously reported that the same allele was associated with an increased risk for development of RA in the Japanese population. Although the association between rs2900180 and joint destruction in RA patients was not validated in our study, we show that an association between TRAF1 locus and joint destruction might exist in Japanese ACPA-negative patients. Our results contribute to the understanding of the pathogenesis of RA, especially in ACPA-negative patients. References: van Steenbergen HW, Rodriguez-Rodriguez L, Berglin E, Zhernakova A, Knevel R, Ivorra-Cortes J, et al. A genetic study on C5-TRAF1 and progression of joint damage in rheumatoid arthritis. Arthritis Res Ther. 2015;17:1. Acknowledgement: We thank all DNA donors for making this study possible. We appreciate the members of Institute of Rheumatology, Tokyo Women's Medical University for their effort on the IORRA cohort. We are also grateful to Ms Kaori Arai for her technical assistance. Disclosure of Interest: None declared